Pengaruh Profitabilitas, Leverage, Reputasi KAP dan Opini Audit terhadap Audit Delay - Alwin Malik Ibrahim; Rosita Suryanigsih (Ultima Accounting : Jurnal Ilmu Akuntansi, 2016)
Financial information which very useful for the investor contained in financial statement which cause the financial statement must be done in timely manner. OJK (Otoritas Jasa Keuangan), an organization which have authorization and legal right on Indonesian stock market require that financial statement must be submitted no later than the end of third month from the latest reporting date. The purpose of this research is to analyze the effect of profitability, leverage, Accountant Public Firm’s reputation, audit opinion towards audit delay. Profitability in this research was measured by Return On Asset (ROA). Leverage was measured by Debt to Equity Ratio (DER). Purposive sampling method was used to determine research sample which result 24 companies which classified in infrastructure, utility and transportation sector listed in Indonesia Stock Exchange for the period 2012-2014. Data was analyzed by using multiple regression analysis. The research result shown that profitability partially has significant effect towards audit delay. Whereas, leverage, accountant public firm’s reputation and auditor’s opinion has not significant effect towards audit delay. Profitability, leverage, accountant public firm’s reputation and audit opinion simultaneously has significant effect towards on audit delay. Keywords: KAP reputation, audit delay, audit opinion, profitability